2022
DOI: 10.3390/biology11101511
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Subcutaneous BCG Vaccination Decreases Atherosclerotic Plaque Number and Plaque Macrophage Content in ApoE−/− Mice

Abstract: Bacille-Calmette Guérin (BCG) modulates atherosclerosis development in experimental animals, but it remains unclear whether neonatal BCG vaccination is pro- or anti-atherogenic. Many animal models differ fundamentally from BCG administration to human infants in terms of age, vaccine preparation, dosing schedule, and route of administration. We aimed to elucidate the effect of neonatal subcutaneous BCG vaccination—analogous to human BCG vaccination—on atherosclerosis development in ApoE−/− mice. At 2 days of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For example, one study evaluated the effect of subcutaneous BCG vaccination on the development of atherosclerosis in ApoE −/− mice. It was found that BCG vaccination reduced plaque number and macrophage content but increased lipid content in a mouse model of atherosclerosis ( 97 ). Similarly, in another animal study, the treatment of BCG killed by extended freeze-drying significantly reduced the size of atherosclerotic lesions, upregulated IL-10 production, and downregulated the expression of pro-inflammatory cytokines (IL-6, IL-13, and TNF-α) in mice ( 98 ).…”
Section: Effect Of Bcg Vaccine On Other Diseasesmentioning
confidence: 99%
“…For example, one study evaluated the effect of subcutaneous BCG vaccination on the development of atherosclerosis in ApoE −/− mice. It was found that BCG vaccination reduced plaque number and macrophage content but increased lipid content in a mouse model of atherosclerosis ( 97 ). Similarly, in another animal study, the treatment of BCG killed by extended freeze-drying significantly reduced the size of atherosclerotic lesions, upregulated IL-10 production, and downregulated the expression of pro-inflammatory cytokines (IL-6, IL-13, and TNF-α) in mice ( 98 ).…”
Section: Effect Of Bcg Vaccine On Other Diseasesmentioning
confidence: 99%